THE INFLUENCE OF AGE, OCCUPATION, NUMBER OF CHILDREN, AND MASS MEDIA ON THE SELECTION OF LONG-TERM CONTRACEPTION METHOD IN NEW CONTRASEPTION ACCEPTORS - Zakkiyatus Zainiyah; Mufarika Mufarika; Imam Gozali (NHM PRESS, 2020)
The Long Term Contraception Method is contraceptive can be used for a long time, effectively, and efficiently. The preliminary study result obtained data on the number of new contraseption acceptors users is 107 participants, but the number of acceptors who chose long-term contraception method (implants and IUD) is very low with the following details: 2 implant participants and 0 IUD participants. The purpose of this study is to analyze the relationship between age, occupation, number of children, and mass media on the selection of long-term contraception method in new contraseption acceptors in Pasean Health Center teritory. The design of this study is analytic with a cross sectional approach. Independent variables are age, occupation, number of children, and mass media. The dependent variable is the sorting of long-term contraception methods. The research population is 107 new contraseption acceptors in Pasean Health Center with 85 sample of new contraseption acceptors using non-probability (purposive sampling). Collecting data used a questionnaire, then analyzed using Spearman Rank. Based on Spearman Rank statistical test results, ρ value: 0.001<α: 0.05 for the age factors relations, ρ value: 0,000<α: 0.05 for the occupation factor relations, ρ value: 0.004<α: 0.05 for number of children relations, and ρ value: 0.001<α: 0.05 for mass media relations. So H0 is rejected and H1 is accepted, there is a relationship between age, occupation, number of children and mass media on the selection of long-term contraception method in the new contraseption acceptors in Pasean Health Center. Based on the results of the study, the women who have more than two children are advised to use long-term contraception method to overcome unwanted child births, if they have enough number of children.